William Wyler : The Life and Films of Hollywood's Most Celebrated Director - Miller, Gabriel, 1948- (Book collections on Project MUSE., 2013)
During his forty-five-year career, William Wyler (1902-1981) pushed the boundaries of filmmaking with his gripping storylines and innovative depth-of-field cinematography. With a body of work that includes such memorable classics as Jezebel (1938), Mrs. Miniver (1942), Ben-Hur (1959), and Funny Girl (1968), Wyler is the most nominated director in the history of the Academy Awards and bears the distinction of having won an Oscar for Best Director on three occasions. Both Bette Davis and Lillian Hellman considered him America's finest director, and Sir Laurence Olivier said he learned more about film acting from Wyler than from anyone else. This book explores the career of one of Hollywood's most unique and influential directors, examining the evolution of his cinematic style.